2011
DOI: 10.1097/inf.0b013e3182271c69
|View full text |Cite
|
Sign up to set email alerts
|

Children With Retinopathy-negative Cerebral Malaria

Abstract: Background Cerebral malaria, defined as otherwise unexplained coma in a patient with circulating parasitemia, is a common disease in the developing world. The clinical diagnosis lacks specificity and children with other underlying causes of coma might be misdiagnosed as having cerebral malaria. The presence of malarial retinopathy can be used to differentiate children whose comas are caused by Plasmodium falciparum and its attendant pathophysiologies from those with other reasons for their abnormal mental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…12,13 The present study adds to these studies with new findings providing additional evidence that the hematopoietic, respiratory, neurologic, and renal systems are involved in both forms of CM, but with more severe involvement in RP CM.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…12,13 The present study adds to these studies with new findings providing additional evidence that the hematopoietic, respiratory, neurologic, and renal systems are involved in both forms of CM, but with more severe involvement in RP CM.…”
Section: Discussionmentioning
confidence: 52%
“…In one prospective autopsy study in Malawi, 23% of children with clinically diagnosed CM were found to have died of other causes, and MR was the only clinical sign to distinguish malarial from nonmalarial cause of death. 6 Previous studies in Malawi have revealed that retinopathy-positive (RP) children have higher rates of respiratory distress and lower hematocrits compared with retinopathy-negative (RN) children and that RN CM children have a shorter febrile prodrome and lower mortality, 12,13 but it remains unclear whether RN CM is a severe nonmalarial illness with incidental parasitemia or a less severe form of the same malarial illness as RP CM. Additionally, MR is found in other types of severe malaria.…”
Section: Introductionmentioning
confidence: 99%
“…We previously hypothesized that at least some of these children may have an asymptomatic malaria parasitemia (reflecting residence in an area of high malaria transmission) along with a second non-malarial cause of their acute illness. 9 Epidemiologically, compared with children with CM who are retinopathy-positive, those who are retinopathy-negative are more likely to be neurologically or developmentally abnormal before admission or have a firstdegree relative with epilepsy. 10 These associations raise the possibility that, because of a genetic pre-disposition or preexisting neurodevelopmental abnormality, at least some children diagnosed with retinopathy-negative CM, when challenged with an infectious pathogen (such as malaria), might be more likely to lapse into coma or have complicated seizures compared with children with retinopathy-positive CM.…”
Section: Introductionmentioning
confidence: 99%
“…10 These associations raise the possibility that, because of a genetic pre-disposition or preexisting neurodevelopmental abnormality, at least some children diagnosed with retinopathy-negative CM, when challenged with an infectious pathogen (such as malaria), might be more likely to lapse into coma or have complicated seizures compared with children with retinopathy-positive CM. 9,10 The Blantyre Malaria Project, located in the Pediatric Research Ward of Queen Elizabeth Central Hospital in Blantyre, Malawi, is a long-standing study of CM pathogenesis. MRI became available at the hospital in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…11 Up to one-third of patients who fulfill WHO case criteria for CM are retinopathy-negative, and it seems likely that these patients have a coma etiology other than malaria. 12 If acute infection with the malaria parasite is not responsible for the coma in retinopathy-negative patients and the underlying cause or causes of these children's comas stays constant in prevalence (is less impacted by rainfall) throughout the calendar year, one would expect the ratio of retinopathy-positive to retinopathy-negative patients to vary seasonally, with retinopathy-positive patients dominating during the high malaria transmission season. In Malawi, uncomplicated malaria usually peaks yearly in January or February, coinciding with the rainy season, and the incidence of malaria infection decreases rapidly as the rains abate ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%